THE USE OF RIDDLES IN PRESCHOOL PEDAGOGICAL DISCOURSE AS A MEANS OF DEVELOPING METAPHORICAL THINKING - Katermina, Veronika; Solovyeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Psycholinguistic studies show that the formation and development of a metaphor in a child's speech occurs during active interaction with an adult and in various activities. It is in pedagogical discourse that, when a child and an adult interact, the latter teaches to detect similarities between different objects, demonstrating transference patterns. In all types of activity, the child's experience of replacing one object with another expands. One of the means of developing figurative thinking in pedagogical discourse is a riddle, which is, in essence, a logical task. Pedagogical discourse actively uses the riddle to achieve a discursive goal: the socialization of a new member of society. In pedagogical preschool discourse, the riddle performs various functions, the main of which are pedagogical, informative, cognitive, playful, axiological. The material for the article was the results of studies devoted to the study of the influence of riddles on the development of figurative thinking in preschool children in pedagogical discourse. As the experimental data have shown, children, composing their riddles, build metaphorical models characteristic of their age: coloristic metaphors, parametric metaphors, anthropomorphic metaphors. The pedagogical value of riddles lies in the fact that they acquaint the child with objects and phenomena, their main features, encourage a deeper delve into the meaning of verbal designation, increase thinking ability, etc. At the same time, the developing potential of riddles is determined by the possibilities inherent in them, and the forms of working with them. Each riddle solved strengthens the child's self-esteem, the desire to repeat success.